Doxorubicin Induces Endotheliotoxicity and Mitochondrial Dysfunction via ROS/eNOS/NO Pathway - He, Huan; Wang, Liang; Qiao, Yang; Zhou, Qing; Li, Hongwei; Chen, Shuping; Yin, Dong; Huang, Qing; He, Ming (Frontiers in Pharmacology, 2020)
Background: Doxorubicin (Dox) can induce endotheliotoxicity and damage the vascular endothelium (VE). The most principle mechanism might be excess reactive oxygen species (ROS) generation. Nevertheless, the characteristics of ROS generation, downstream mechanisms, and target organelles in Dox-induced endotheliotoxicity have yet to be elucidated. Methods and Results: In order to explore the related problems, the VE injury models were established in mice and human umbilical vein endothelial cells (HUVECs) by Dox-induced endotheliotoxicity. Results showed that the activities of lactate dehydrogenase (LDH) and creatine kinase of mice’s serum increased after injected Dox. The thoracic aortic strips’ endothelium-dependent dilation was significantly impaired, seen noticeable inflammatory changes, and brown TUNEL-positive staining in microscopy. After Dox-treated, HUVECs viability lowered, LDH and caspase-3 activities, and apoptotic cells increased. Both intracellular/mitochondrial ROS generation significantly increased, and intracellular ROS generation lagged behind mitochondria. HUVECs treated with Dox plus ciclosporin A (CsA) could basically terminate ROS burst, but plus edaravone (EDA) could only delay or inhibit, but could not completely cancel ROS burst. Meanwhile, the expression of endothelial nitric oxide synthase (eNOS) decreased, especially phosphorylation of eNOS significantly. Then nitric oxide content decreased, the mitochondrial function was impaired, mitochondrial membrane potential (MMP) impeded, mitochondrial swelled, mitochondrial permeability transition pore (mPTP) was opened, and cytochrome C was released from mitochondria into the cytosol. Conclusion: Dox produces excess ROS in the mitochondria, thereby weakens the MMP, opens mPTP, activates the ROS-induced ROS release mechanism, induces ROS burst, leads to mitochondrial dysfunction, which in turn damages VE. Therefore, interrupting any step of the cycles, as mentioned above, can end the related vicious cycle and prevent the occurrence and development of injury.